Fat Attenuation Index of Renal Cell Carcinoma Reveals Biological Characteristics and Survival Outcome - Wang, Hongkai; Wei, Yu; Hu, Xiaoxin; Pan, Jian; Wu, Junlong; Wang, Beihe; Zhang, Hailiang; Shi, Guohai; Liu, Xiaohang; Zhao, Jinou; Zhu, Yao; Ye, Dingwei (Frontiers in Oncology, 2022)
Purpose: The CT fat attenuation index (FAI) is an ideal quantifiable imaging factor to identify the inflammation degree of peri-tumor adipose tissue. We aimed to verify whether FAI could reflect peri-tumor adipose inflammation and predict survival outcome of renal cell carcinoma (RCC), discover transcriptomic features of tumor tissues and adjacent adipocytes. Materials and Methods: Two clinical cohort (Fudan University Shanghai Cancer Center [FUSCC] cohort [N=129] and TCGA cohort [N=218]) were used to validate the association between FAI and clinical outcome. A prospective cohort (N=19) was used to discover the molecular phenotyping of peri-tumor adipose tissue and tumor tissue according to their FAI value. A clinical cohort (N=32) in which patients received cyto-reductive surgery was used to reveal the dynamic change of FAI. Results: A high peri-tumor FAI was significantly associated with worse outcome in both FUSCC (HR=2.28, p=0.01) and TCGA cohort (HR=2.24, p<0.001). Analysis of RNA expression of paired RCC tissue and peri-tumor fat tissue showed synchronized alterations in pathways such as cytokine-cytokine receptor interaction and complement and coagulation cascades. RCC tissues showed significant alterations in the neuroactive ligand-receptor interaction pathway. Immune deconvolution analysis showed enhanced infiltration of macrophages in high FAI tumor tissues, together with lower angiogenesis level. We also observed synchronous dynamic changes in FAI and tumor size after targeted therapy. Conclusions: FAI could reflect the biological characteristics and tumor immune micro-environment of both the tumor and the peri-tumor adipose in RCC. High peri-tumor FAI had the potential to predict worse survival outcome in RCC patients.